2020
DOI: 10.1111/jsr.13123
|View full text |Cite
|
Sign up to set email alerts
|

Telephone‐guided imagery rehearsal therapy for nightmares: Efficacy and mediator of change

Abstract: According to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), nightmares are well remembered, dysphoric dreams that often lead to awakening (American Psychiatric Association, 2013). To fulfil the criteria for nightmare disorder, the nightmares should not be explained by other factors, and they should cause significant clinical distress in daily life.Nightmares can be of idiopathic (with no specific origin) or post-traumatic nature. Two−five percent of the general population rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The finding that a single-session intervention can help people with nightmares has been reported previously [19,29]. Recently, Lancee et al [22] also showed that IRT is effective with little time investment: in their study, IRT was delivered within three 15-minute telephone sessions combined with self-help. Thus, a very short treatment is enough to achieve effects, only a few people need a longer therapy.…”
Section: Effectivenessmentioning
confidence: 84%
See 2 more Smart Citations
“…The finding that a single-session intervention can help people with nightmares has been reported previously [19,29]. Recently, Lancee et al [22] also showed that IRT is effective with little time investment: in their study, IRT was delivered within three 15-minute telephone sessions combined with self-help. Thus, a very short treatment is enough to achieve effects, only a few people need a longer therapy.…”
Section: Effectivenessmentioning
confidence: 84%
“…In a recent study by Lancee et al testing telephone-guided IRT, the waiting-list control group had an effect size of d = 0.08 for log-transformed nightmare frequency (where the IRT group had an effect size of d = 1.11). The waiting-list group's effect size for nightmare distress was d = 1.12, while the IRT group had an effect size of d = 1.87 [22]. Taking into account the effect sizes of the control groups of similar studies, it can be strongly assumed that the current method had an effect although there was no control group.…”
Section: Effectivenessmentioning
confidence: 96%
See 1 more Smart Citation
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted February 19, 2022. ; https://doi.org/10.1101/2022.02.17.22270256 doi: medRxiv preprint reduces nightmare frequency and distress (47,48), negative emotions in dreams (50), while improving sleep quality (47,51), insomnia severity (52), mood scores (47,53), and PTSD severity (47,48). However, although IRT is the established treatment of nightmares since more than 30 years now (15), the lack of a control group (without IRT) in the current study design cannot exclude that the clinical improvements observed in both patients groups was influenced by other factors (e.g., patient expectations).…”
Section: Discussionmentioning
confidence: 99%
“…Lancee, Effting, and Kunze (2021) from Amsterdam and Munich conducted a study to test whether telephone‐guided imagery rehearsal therapy (IRT) for nightmares might be an effective treatment for people suffering from nightmares. IRT was introduced decades ago as a very successful treatment avenue to deal with recurrent nightmares, either idiopathic or as a part of post‐traumatic stress disorder.…”
mentioning
confidence: 99%